ANALISIS TINDAK TUTUR DAN PRINSIP KERJA SAMA PADA PEMBELAJARAN DISKUSI SISWA KELAS IX SMP PGRI 400 TANGERANG - Haryanti, Reni; Sulaeman, Agus; Goziyah, Goziyah (Universitas Muhammadiyah Tangerang, 2023)
The use of utterances that contain cooperative principle maxims and speech acts, be it locutions, illocutions or perlocutions, of course, have different aims and objectives depending on the context of the utterance. In class IX student discussion activities, utterances that contain the maxim of the principle of cooperation are intended for cohesiveness or togetherness in discussion activities. So, based on this, discussion activities can run smoothly and important information discussed in the discussion will be conveyed clearly